Successful ablation of coexistent mahaim tachycardia and right posterior accessory pathway in a patient with ebstein's anomaly - Gül, Enes Elvin; Akdeniz, Celal; Tuzcu, Volkan (Elsevier Ireland Ltd, 2013)
The atriofascicular accessory pathway (AP) referred as the Mahaim pathway is rare form of preexcitation. Mahaim AP is characterized with decremental anterograde-only conduction and antidromic tachycardia with LBBB morphology. The prevalence of Mahaim AP in Ebstein’s anomaly is significantly high. In this case, we report coexistence of Mahaim AP and manifest WPW in a patient with Ebstein’s anomaly who was successfully ablated without fluoroscopy.
WOS: 000317946500481
Keywords: Successful Ablation; Coexistent Mahaim; Tachycardia and Right; Posterior; Accessory Pathway